Prognostic Significance of Lactate Dehydrogenase in Patients Undergoing Surgical Resection for Laryngeal Squamous Cell Carcinoma - Erliang Guo MD; Lunhua Guo MD; Changming An MD; Cong Zhang MD; Kaibin Song MD; Guohui Wang MD; Chunbin Duan MD; Xiwei Zhang MD; Xianguang Yang MD; Zhennan Yuan MD; Junnan Guo MD; Ji Sun MD; et al. (Cancer Control, 2020)
The aim is to estimate the prognostic value of lactate dehydrogenase (LDH) in patients undergoing surgical resection for laryngeal squamous cell carcinoma (LSCC). A total of 640 resected LSCC patients were included. Preoperative lactate dehydrogenase (LDH) was assessed. Kaplan-Meier survival analysis and Cox regression analysis were conducted for overall survival (OS) and recurrence-free survival (RFS). Kaplan-Meier analysis, univariate analysis and multivariate analysis demonstrated significant prognostic value for preoperative LDH. Although LDH was predictor of OS, it failed to be a predictor of RFS. The univariate HR and 95% CI of LDH were 0.484 and 0.357-0.658 (P < 0.0001). The multivariate analysis showed that LDH (HR = 0.518, 95% CI: 0.380-0.705, p < 0.0001) was related to OS. Elevated preoperative LDH >132 IU/L was significantly associated with better survival. Preoperative LDH might be an independent prognostic marker of OS in LSCC patients undergoing surgical resection.